Perioperative Bilateral Medial Medullary Infarction With “Snake Eyes Appearance”: A Case Report - Xu, Yicheng; Li, Ke; Yao, Xinlu; Yang, Qiyan; Wang, Peifu (Frontiers in Medicine, 2021)
Perioperative bilateral medial medullary infarction (BMMI) cases mimicking acute motor axonal neuropathy (AMAN) under general anesthesia have not been reported. We describe a patient who suffered flaccid quadriplegia and could not wean from mechanical ventilation after emergence from general anesthesia in cardiac surgery. A diagnosis of AMAN was considered, but intravenous immunoglobulin showed little efficacy. Magnetic resonance imaging of the patient later revealed BMMI with “snake eyes appearance”, and he was found to have severe vertebral artery stenosis. Considering the association between severe coronary heart disease and cerebrovascular stenosis, we highlight the significance of preoperative evaluation and comprehensive management of the cerebrovascular system for certain patients.